Peace Education, Religious Discourse, and Scientific Enquiry: Dialogue and Collaboration from Eastern European Contexts (Routledge, 2025)
Empowering educators and policymakers to effect positive change in their communities, this book critically examines how sustained dialogue and cooperation between scientific inquiry and religious discourse can contribute to the fostering of successful peace education initiatives. Providing an overview of the historical and cultural context of peace education in Eastern Europe, the chapters look initially at the theoretical foundations, emphasising the need for empathy, internal peace, and traditional values. Featuring contributions from the United States, Germany, Italy, Slovakia, Turkey, and Poland, subsequent sections outline ethical, moral, and religious dimensions to inform effective peace education strategies, along with a discussion on how they can be harmonised with secular approaches to provide a holistic framework for peace education. Case studies and practical applications follow, ranging from Maria Montessori’s educational approach to the role of social media and sustainability in peace education, providing readers with a comprehensive understanding of how different perspectives can inform effective peace education strategies. With implications and take aways for educators and researchers looking to foster a culture of peace and non-violence, this book will be of interest to scholars, policymakers, postgraduate students, and curriculum designers in the fields of peace education, values education, conflict resolution, and social cohesion more broadly. Those working in peacebuilding organisations and NGOs more widely may also benefit from the chapters.